2002
DOI: 10.1159/000066390
|View full text |Cite
|
Sign up to set email alerts
|

Major Depression with Ischemic Heart Disease: Effects of Paroxetine and Nortriptyline on Measures of Nonlinearity and Chaos of Heart Rate

Abstract: Depression is associated with increased cardiovascular mortality in patients with preexisting cardiac illness. A decrease in cardiac vagal function as suggested by a decrease in heart rate variability (HRV) or heart period variability has been linked to sudden death in patients with cardiac disease as well as in normal controls. Recent studies have shown decreased vagal function in cardiac patients with depression as well as in depressed patients without cardiac illness. In this study, we compared 20 h awake a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
0
3

Year Published

2003
2003
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(48 citation statements)
references
References 97 publications
2
43
0
3
Order By: Relevance
“…This concept fits well with the observation that patients suffering from depression after myocardial infarction are at a significantly higher risk for sudden death than their non-depressed counterparts (Lown and Verrier 1976). It is also in line with previous studies describing a heart rate lowering effect of SSRIs such as fluoxetine, paroxetine and citalopram (Roose et al 1998;Rasmussen et al 1999;Yeragani et al 2002). Interestingly, it has been shown that sertraline treatment in patients suffering from major depression after acute myocardial infarction was associated with reduced ventricular ectopic activity and facilitation of recovery of cardiac autonomic function (Shapiro et al 1999;McFarlane et al 2001).…”
Section: Autonomic Functionssupporting
confidence: 91%
“…This concept fits well with the observation that patients suffering from depression after myocardial infarction are at a significantly higher risk for sudden death than their non-depressed counterparts (Lown and Verrier 1976). It is also in line with previous studies describing a heart rate lowering effect of SSRIs such as fluoxetine, paroxetine and citalopram (Roose et al 1998;Rasmussen et al 1999;Yeragani et al 2002). Interestingly, it has been shown that sertraline treatment in patients suffering from major depression after acute myocardial infarction was associated with reduced ventricular ectopic activity and facilitation of recovery of cardiac autonomic function (Shapiro et al 1999;McFarlane et al 2001).…”
Section: Autonomic Functionssupporting
confidence: 91%
“…A number of studies showed that antidepressant treatment impacted on HRV. Tricyclic antidepressants (TCAs) reduced parasympathetic tone and decreased HRV (22,24,56,58). Nortriptyline was reported to decrease sympathetic activity in patients under awake and sleeping conditions and decreased vagal activity in the awaking condition (58).…”
Section: Discussionmentioning
confidence: 99%
“…Our findings are important especially in view of the reports of increased side effects of TCAs such as nortriptyline that has stronger vagolytic effects on cardiac autonomic function compared with paroxetine, a SSRI drug. [2] But sertraline may have some cardio-protective effects against arrhythmia due to ouabain toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…[1,2] TCAs exert a significant increase in QT variability that is associated with ventricular arrhythmia. [3] The newer antidepressant compounds, selective serotonin reuptake inhibitor (SSRI) drugs are widely used as antidepressants in treating patients.…”
Section: Introductionmentioning
confidence: 99%